Experimental Polarizability Transition Moments of CO2 for Excited Vibrational States - Carlos Álvarez; Guzmán Tejeda; José M. Fernández (Molecules)
The Raman spectrum of CO2 from room temperature to 1800 K has been measured in a series of experiments. The differential Raman scattering cross-sections for the fundamental bands at 1285.41 cm−1 and 1388.18 cm−1 have been obtained from reference bands of H2 and N2 as intensity standards. The Raman cross-sections of CO2 hot bands, involving vibrational energy levels up to 5000 cm−1, were derived from those of the fundamental bands. The Raman cross-sections obtained this way were reduced to transition moments of the mean molecular polarizability, which make it possible to simulate the Raman spectrum of CO2 up to 2000 K. This paves the way for local or remote diagnostics of CO2 in hot environments using Raman based techniques.